Wear characteristics of exfoliated MoS2/polyamide-6, 6 composite. (March 2022) - Kim, Jae Ik; Kim, Jung W; Ryu, Sung H
Effect of exfoliation of MoS2 on the wear characteristics of the MoS2 /PA-6, 6 composite is investigated. Exfoliation of MoS2 is identified using X-ray diffraction, Raman spectroscopy, and transmission electron microscopy. Wear loss of composites is done using Taber abrasion tester with CS-17 abrasive wheel and atomic force microscope is used to characterize the worn surface. It is observed that wear loss of MoS2 /PA-6, 6 composite is strongly affected by content and exfoliation of MoS2 . Wear loss of composites is decreased by the addition of MoS2 irrespective of exfoliation and it is improved with increasing filler content. Exfoliated MoS2 /PA-6, 6 composites show improved wear characteristic, that is, reduced wear loss, compared to the pristine MoS2 /PA-6, 6 composite. Addition of MoS2 induces less plastic deformation of the worn surface of composites, and it is more distinct for exfoliated MoS2 .